2016
DOI: 10.1073/pnas.1613055113
|View full text |Cite
|
Sign up to set email alerts
|

Context-specific inhibition of translation by ribosomal antibiotics targeting the peptidyl transferase center

Abstract: The first broad-spectrum antibiotic chloramphenicol and one of the newest clinically important antibacterials, linezolid, inhibit protein synthesis by targeting the peptidyl transferase center of the bacterial ribosome. Because antibiotic binding should prevent the placement of aminoacyl-tRNA in the catalytic site, it is commonly assumed that these drugs are universal inhibitors of peptidyl transfer and should readily block the formation of every peptide bond. However, our in vitro experiments showed that chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
162
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(182 citation statements)
references
References 46 publications
(59 reference statements)
9
162
0
1
Order By: Relevance
“…The inhibition of protein synthesis by CLM depends on the amino-acid sequence of the nascent peptide and the identity of the aminoacyl-tRNA with the most efficient arrests occurring after alanine (and to a lesser extent after serine or threonine) that appear at the penultimate position of the nascent chain [9]. To test whether the specificity of action of AA-CAM compounds matches that of CLM, we used primer extension inhibition assay (toe-printing) to check whether the derivatives that exhibited inhibitory activity in the PURE system (Figure 2C), would arrest the ribosome at the same codon(s) where translation is arrested by CLM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibition of protein synthesis by CLM depends on the amino-acid sequence of the nascent peptide and the identity of the aminoacyl-tRNA with the most efficient arrests occurring after alanine (and to a lesser extent after serine or threonine) that appear at the penultimate position of the nascent chain [9]. To test whether the specificity of action of AA-CAM compounds matches that of CLM, we used primer extension inhibition assay (toe-printing) to check whether the derivatives that exhibited inhibitory activity in the PURE system (Figure 2C), would arrest the ribosome at the same codon(s) where translation is arrested by CLM.…”
Section: Resultsmentioning
confidence: 99%
“…CLM was originally viewed as a universal inhibitor of peptide bond formation [8]. However, this model has been recently revised because the newer data revealed CLM as a context-specific inhibitor of translation, whose activity depends on the nature of specific amino acids in the nascent chain and the identity of the residue entering the A site [9]. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these compounds almost exclusively act as broad-spectrum inhibitors, displaying little sequence specificity 4 . Many studies have revealed how these compounds bind the translating ribosome and inhibit its function [5][6][7][8][9] . Recently, we described the small molecule PF846 that selectively blocks the translation of individual mRNAs by the human ribosome 10 .…”
Section: Main Textmentioning
confidence: 99%
“…Some studies hypothesize a length of 23 or 24 nucleotides due to this being the most common fragment length [6,22,23]. In contrast, other studies including a few of those examined here use 'ribosomal footprint' in a much larger range of up to 42 nucleotides [9,10,24]. Now the question of the RNases useful for ribosome footprinting arises.…”
Section: Ribosomal Footprint Generationmentioning
confidence: 95%
“…With this method no ribosomal accumulation at the translational start site is observed [6,8]. Three studies included in our survey used filtration and flash freezing [9][10][11].…”
Section: Introductionmentioning
confidence: 99%